MPH Capstone experiences: promising practices and lessons learned - Landfried, Meg; Chen, Elizabeth; Savelli, Lindsay Bau; Cooper, Morgan; Price, Brittany Nicole; Emmerling, Dane (Frontiers in Public Health, 2023)
To ensure workforce readiness, graduate-level public health training programs must prepare students to collaborate with communities on improving public health practice and tools. The Council on Education for Public Health (CEPH) requires Master of Public Health (MPH) students to complete an Integrative Learning Experience (ILE) at the end of their program of study that yields a high-quality written product demonstrating synthesis of competencies. CEPH suggests written products ideally be “developed and delivered in a manner that is useful to external stakeholders, such as non-profit or governmental organizations.” However, there are limited examples of the ILE pedagogies and practices most likely to yield mutual benefit for students and community partners. To address this gap, we describe a community-led, year-long, group-based ILE for MPH students, called Capstone. This service-learning course aims to (1) increase capacity of students and partner organizations to address public health issues and promote health equity; (2) create new or improved public health resources, programs, services, and policies that promote health equity; (3) enhance student preparedness and marketability for careers in public health; and (4) strengthen campus-community partnerships. Since 2009, 127 Capstone teams affiliated with the Department of Health Behavior at the Gillings School of Global Public Health at The University of North Carolina at Chapel Hill have worked with seventy-nine partner organizations to provide over 103,000 h of in-kind service and produce 635 unique products or “deliverables.” This paper describes key promising practices of Capstone, specifically its staffing model; approach to project recruitment, selection, and matching; course format; and assignments. Using course evaluation data, we summarize student and community partner outcomes. Next, we share lessons learned from 13 years of program implementation and future directions for continuing to maximize student and community partner benefits. Finally, we provide recommendations for other programs interested in replicating the Capstone model.